Normative Ideology, Transgressive Aesthetics: Depicting and Exploring the Urban Underworld in Oliver Twist (1838), Twist (2003) and Boy Called Twist (2004) - Clémence Folléa (Cahiers Victoriens et Edouardiens)
In his preface to Oliver Twist, Dickens insists that his depiction of the London underworld is deprived of ‘allurements and fascinations’, and states his didactic ambition to offer a realistic description of this grim universe. Yet, in many ways, the text itself is led astray from this normative path, and the aesthetics of Oliver Twist’s criminal world thwarts the ideology expressed in the preface. After having examined how Dickens’s novel is fundamentally structured by an interplay of norms and transgressions, I propose to look at two recent adaptations which fully appropriate the ambivalence of their source text. Twist and Boy Called Twist both respond to the didactic ideology of Oliver Twist and make the most of the novel’s subversive potential. In the end, these two films deploy many latent aspects of the text, thus redefining the terms in which we read Oliver Twist. By breaking away from traditional readings of the novel, they transgress our relation to this canonical text, which continues to resist attempts at normalisation and normative interpretations. This paper takes into account not only the aesthetics of these adaptations but also their contexts of production, in which Oliver Twist’s potential for resistance takes on new meanings and new purposes.